EFFECT OF BIOSTIMULANT (NOVOBAC) ON ROOT CHARACTER SOF CHILLLI (CAPSICUM ANNUUM L.) - S. JIDHU VAISHNAVI; P. JEYAKUMAR; C. N. CHANDRASEKHAR (The Bioscan, 2015)
The increasing use of chemicals from the stage of germination to harvest of the crop affects the soil condition and productivity of crops. This can be reduced by the application of microorganisms which act as biocontrol agents for pest and disease as well as biostimulants. Combination of several beneficial microorganisms when applied as seed treatments and soil drenching has profound effect on root characters of chilli. It was observed that seed treatment withNovoBac@ 2g/kg + soil drenching @ 500 g/ha improvedviz.,root characters like root length, root volume, root dry weight, root shoot ratio and also transplanting survival rate of chilli.